Marta versus Neymar: The ‘war of the sexes’ at the 2016 Olympic games in the narratives of sports journalism in Brazil - Helal, Ronaldo George; da Costa, Leda Maria (Eracle. Journal of Sport and Social Sciences, 2024)
When the men’s and women’s football teams participate simultaneously in the same or different competitions, it is common for Brazilian sports journalism to construct narratives based on the comparison between the performance of both teams. At the 2016 Olympic Games, this phenomenon set up a kind of ’war of the sexes’ staged in the narratives of important newspapers in the country and even chanted in the stadium stands. The protagonists of this duel were the players Neymar and Marta, both number 10 of the Brazilian men’s and women’s teams, and both national and international idols. This article aims to analyse this ’war of the sexes’. For this purpose, we chose the press coverage of the 2016 Games by the newspapers O Globo and Folha de São Paulo, two of the most traditional periodicals in Brazil and those with the largest national circulation.